A A User Experience-Centered Design Framework for Optimizing English Learning on All-in-One Multimedia PC - Shan, Qiaojuan (Journal of Islamic Elementary Education, 2025)
This research aims to develop a user experience (UX)-centered design framework for educational content delivered through All-in-One Multimedia Personal Computers (AOMPCs), focusing specifically on optimizing English learning and enhancing teaching effectiveness. By analyzing existing AOMPC-based English learning applications, the research explores how content presentation influences students' motivation, classroom engagement, and academic performance. The findings reveal that user experience optimization relies on multiple interrelated dimensions, including interface design, interactivity, visual aesthetics, and multimedia integration. These elements collectively shape a more engaging and immersive learning environment. Furthermore, the study integrates theoretical perspectives with empirical data to identify core drivers of an effective AOMPC learning experience, such as real-time feedback, adaptive content, and interactive task design. These factors significantly elevate learner motivation and cognitive engagement. The study not only offers practical insights for designing multimedia teaching tools but also contributes a theoretical foundation for future research and innovation in educational technology.